Hospital discharge of elderly patients to primary health care, with and without an intermediate care hospital – a qualitative study of health professionals’ experiences - Unni Alice Dahl; Aslak Steinsbekk; Svanhild Jenssen; Roar Johnsen (International Journal of Integrated Care, 2014)
Introduction: Intermediate care is an organisational approach to improve the coordination of health care services between health care levels. In Central Norway an intermediate care hospital was established in a municipality to improve discharge from a general hospital to primary health care. The aim of this study was to investigate how health professionals experienced hospital discharge of elderly patients to primary health care with and without an intermediate care hospital.  Methods: A qualitative study with data collected through semi-structured focus groups and individual interviews. Results: Discharge via the intermediate care hospital was contrasted favourably compared to discharge directly from hospital to primary health care. Although increased capacity to receive patients from hospital and prepare them for discharge to primary health care was viewed as a benefit, professionals still requested better communication with the preceding care level concerning further treatment and care for the elderly patients. Conclusions: The intermediate care hospital reduced the coordination challenges during discharge of elderly patients from hospital to primary health care. Nevertheless, the intermediate care was experienced more like an extension of hospital than an included part of primary health care and did not meet the need for communication across care levels.